Cryptocurrency Market Reactions to Regulatory News - Raphael A. Auer; Stijn Claessens (Center for Economic Studies and ifo Institute (CESifo), 2020)
Cryptocurrencies are often thought to operate out of the reach of national regulation, but in fact their valuations, transaction volumes and user bases react substantially to news about regulatory actions. The impact depends on the specific regulatory category to which the news relates: events related to general bans on cryptocurrencies or to their treatment under securities law have the greatest adverse effect, followed by news on combating money laundering and the financing of terrorism, and on restricting the interoperability of cryptocurrencies with regulated markets. News pointing to the establishment of specific legal frameworks tailored to cryptocurrencies and initial coin offerings coincides with strong market gains. These results suggest that cryptocurrency markets rely on regulated financial institutions to operate and that these markets are segmented across jurisdictions.
Keywords: E42; E51; F31; G12; G28; G32; G38; 330; digital currencies; cryptocurrencies; bitcoin; ethereum; distributed ledger technology; regulation; financial markets; event studies